Public Trusts as an Instrument of Financial Administration and Government Transparency: Evidence from The State of Sonora - Cynthia Zaraith Orozco Atondo; Nallely Esther Villa Ruiz; Alma Yesenia Maytorena Terán; Isaac Yael Tostado Cortez (Revista de Gestão Social e Ambiental, 2026)
Objective: To analyze the role of public trusts as financial management instruments in the State of Sonora, identifying their contribution to the efficient management of public resources, accountability, and compliance with the regulatory framework regarding access to information. Theoretical framework: The research is grounded in public administration theory, government financial management, accountability, and transparency, as well as the Mexican legal framework applicable to public trusts. Method: A qualitative study with a descriptive and documentary scope was conducted, complemented by semi-structured interviews with specialists involved in the administration of two public trusts in the State of Sonora, representing both the government sector and the trustee institution. Data were analyzed through a review of regulations and content analysis. Results and discussion: The results demonstrate that public trusts strengthen financial management through control mechanisms involving technical committees, audits, and transparency obligations. Research implications: The findings provide evidence to strengthen transparency policies, improve the financial management of public trusts, and support decision-making within state administrations, thereby fostering greater public trust in the use of public resources. Originality/Value: The study’s main contribution lies in demonstrating that public trusts serve as effective mechanisms for financial management and governance when operating under principles of transparency, institutional control, and accountability.